2012
DOI: 10.1128/aac.01641-12
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Genetic Diversity within the Mycobacterium tuberculosis Complex for the Development of Novel Antibiotics and Diagnostic Tests of Drug Resistance

Abstract: e Despite being genetically monomorphic, the limited genetic diversity within the Mycobacterium tuberculosis complex (MTBC) has practical consequences for molecular methods for drug susceptibility testing and for the use of current antibiotics and those in clinical trials. It renders some representatives of MTBC intrinsically resistant against one or multiple antibiotics and affects the spectrum and consequences of resistance mutations selected for during treatment. Moreover, neutral or silent changes within g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 168 publications
(166 reference statements)
2
67
0
Order By: Relevance
“…However, susceptibility to ofloxacin can be restored by additional mutations in the gene that infers hypersensitivity. 261 Therefore, strains should be checked for the resistance-conferring mutations and the restorative compensatory mutations. Although this phenomenon is rare, it has great significance for patients, because a false-positive test for fluoroquinolone resistance could result in a misdiagnosis of XDR tuberculosis and unnecessary treatment with drugs of heightened toxicity.…”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…However, susceptibility to ofloxacin can be restored by additional mutations in the gene that infers hypersensitivity. 261 Therefore, strains should be checked for the resistance-conferring mutations and the restorative compensatory mutations. Although this phenomenon is rare, it has great significance for patients, because a false-positive test for fluoroquinolone resistance could result in a misdiagnosis of XDR tuberculosis and unnecessary treatment with drugs of heightened toxicity.…”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…Thus, understanding the metabolic flux of one particular strain, including a long-term lab-adapted strain, such as H37Rv, does not guarantee that we understand the individual metabolic nuances of all strains. We and others have previously highlighted the importance of considering the impact of M. tuberculosis genetic and metabolic diversity in the generation of future treatment and diagnostic programs (2,4,28,66,67).…”
Section: Fig 6 the Dost Defect In Beijing Isolates Has No Impact On Tmentioning
confidence: 99%
“…In the same paper, modeling simulations used by Ford et al indicated that the probability of de novo MDR arising in patients infected with Beijing strains is more than 20-fold higher than for non-Beijing strain infections (13). Although the exact mechanism(s) underlying this enhanced mutation rate has yet to be defined, we and other groups have suggested that perturbations in regulatory, metabolic, or structural pathways that exist in the Beijing strains potentially account for an alteration in antibiotic sensitivity/tolerance (2,11,13,14). In turn, this could provide a mechanism by which an increased proportion of cells are able to survive drug exposure, thereby increasing the potential for the acquisition of specific resistance mutations (15).…”
mentioning
confidence: 99%
“…However, the genotypic diversity and geographical distribution of Mycobacterium tuberculosis complex (MTBC), together with the inability to provide appropriate interpretation of silent mutations and the limited versatility are some of the restraints undermining the effectiveness of the current tools on a global scale (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%